2010
DOI: 10.1155/2011/696741
|View full text |Cite
|
Sign up to set email alerts
|

An Unsupervised and Drift-Adaptive Spike Detection Algorithm Based on Hybrid Blind Beamforming

Abstract: In the case of extracellular recordings, spike detection algorithms are necessary in order to retrieve information about neuronal activity from the data. We present a new spike detection algorithm which is based on methods from the field of blind equalization and beamforming and which is particularly adapted to the specific signal structure neuronal data exhibit. In contrast to existing approaches, our method blindly estimates several waveforms directly from the data, selects automatically an appropriate detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Even though this approach is computationally intensive (section 3.3), our results suggest that directly looking for an action potential waveform shape in the continuous voltage time series is better for spike detection than approaches we compared against. Conceptually, using a matched filter [11,54,[74][75][76] is very similar to our approach in that it looks for the waveform shape directly. However, our analysis of the matched filter found that it did not perform as well as the HMM, though more recent work [77] may address the shortcomings of matched filters.…”
Section: Related Methodsmentioning
confidence: 99%
“…Even though this approach is computationally intensive (section 3.3), our results suggest that directly looking for an action potential waveform shape in the continuous voltage time series is better for spike detection than approaches we compared against. Conceptually, using a matched filter [11,54,[74][75][76] is very similar to our approach in that it looks for the waveform shape directly. However, our analysis of the matched filter found that it did not perform as well as the HMM, though more recent work [77] may address the shortcomings of matched filters.…”
Section: Related Methodsmentioning
confidence: 99%